Pemanfaatan Buku Saku Posyandu Remaja Dalam Meningkatkan Pengetahuan Kesehatan Reproduksi Remaja - Rosalinna; Triwik Srimulati; Ari kurniarum; Kuswati; Endah Widhi Astuti; Sih Rini Handajani; Paryono (Universitas Muhammadiyah Klaten, 2023)
Adolescent health issues are an important issue because adolescents will be the next generation so that adolescent reproductive health can be an indicator of future health. One of the adolescent health problems is fertility or birth in adolescents, which is an important issue because it is related to the level of morbidity and mortality of mothers and children. Teenage mothers are more at risk of experiencing health problems and death related to childbirth compared to older women. The age-specific birth rate or Age Specific Fertility Rate (ASFR) for young women aged 15-19 years in Indonesia is relatively high, reaching 36 per 1,000 women. Efforts to increase human resources through training in the use of Pocket Books at Youth Posyandu. Analysis of the situation, in Mentuk Kidul Village, Klaten Regency, data was obtained: as many as 20 out of 50 teenagers experienced anemia nutritional problems, 30 teenagers experienced dysmenorrhea during menstruation, and as many as 10% of early marriages occurred. from teenagers. The method is to empower the community, especially teenagers, in using pocket books as an effort to increase teenagers' health knowledge for the continuity of implementing youth mentoring in collaboration with the village midwife. The methods used in this Community Service are brainstorming, group discussions, and practical demonstrations. The results of the activity showed that the average knowledge before the pocket book intervention was carried out was 47.12 ± 4.5, after the pocket book intervention was carried out, it was found that adolescents' knowledge about reproductive health increased to 81.23 ± 8.12. Statistical results show significant results. Increased knowledge before and after the adolescent reproductive health pocket book intervention at the Youth Posyandu in Mentuk Kidul Village, Klaten Regency. Pocket book is effective for increasing teenagers' knowledge in youth Posyandu.